A study of the incidence of posterior reversible encephalopathy syndrome in patients with eclampsia and their fetomaternal outcome at a tertiary care centre in India - Lewis, Preeti F.; Sehgal, Roopali; Bavdekar, Nitin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Hypertensive disorders are one of the most crucial and still unsolved problems in obstetrics. Eclampsia is one of the most serious acute complications of pregnancy, and the risk of morbidity and mortality for both the mother and baby is very high. Posterior Reversible Encephalopathy Syndrome (PRES) is a neurological condition associated with eclampsia that can have severe consequences if not promptly diagnosed and managed. It presents with altered consciousness, acute cortical blindness and convulsions. “Delivery is the ultimate cure of eclampsia” is a traditional belief but it does occur in the postpartum period too. Methods: A retrospective analysis of medical records was conducted for eclamptic patients admitted to the tertiary care center over a specified period. Patients diagnosed with PRES were identified and their clinical characteristics, diagnostic imaging findings, treatment modalities, and maternal and neonatal outcomes were reviewed. Results: This study sheds light on the incidence of posterior reversible encephalopathy syndrome in eclamptic patients at a tertiary care center in India. PRES was more common in primigravidas in the younger age group (20-30 years) and patients who presented with multiple seizures, resulting in higher number of cesarean sections. Conclusions: Early recognition and management of PRES are crucial for improving maternal outcomes. Further research is warranted to refine strategies for timely diagnosis and intervention, ultimately contributing to the reduction of maternal and neonatal morbidity and mortality associated with eclampsia and its complications.